Mitragynine-Induced Conditioned Place Preference (CPP) And The Profiles Of Dopamine And Its Metabolites In Rats - Yusoff, Nurul Hasnida Mohammad (2018)
Mitragyna speciosa (M. speciosa) Korth is a traditional herbal plant indigenous to Southeast Asia. Regular use of this plant by human may lead to addiction with profound withdrawal symptoms. It is hypothesized that the abuse of M. speciosa preparations could be attributed to mitragynine, the main psychoactive compound isolated from its leaves. Therefore, comprehensive studies on the rewarding properties of mitragynine, as well as the mechanisms invoved, are needed. In the first part of the study, the rewarding properties of mitragynine (1, 5, 10 and 30 mg/kg) and its locomotor effects were investigated in Sprague-Dawley rats, using a conditioned place preference (CPP) paradigm.